Comprehensive advances in phytochemical components, bioactive functionality, and processing applications of mustard (Brassica juncea (L.) Czern.): a review - Hu, Yuao; Yan, Zhengyu (Frontiers in Nutrition, 2025)
Mustard (Brassica juncea (L.) Czern.), a globally cultivated cruciferous species, is a rich source of bioactive phytochemicals, including glucosinolates (GSLs), phenolic compounds, and erucic acid (EA), which collectively contribute to its multifunctional applications in nutrition, medicine, and food processing. This review systematically elucidates the phytochemical profiles and biological activities of B. juncea, emphasizing structure–function relationships and processing optimization. Key phytochemical components, such as GSLs and their enzymatic degradation products, exhibit potent antioxidant, anti-inflammatory, and anticancer properties. Advanced processing techniques, including fermentation, low-sodium brining, and high-pressure treatment, are highlighted for enhancing functional compound stability and bioavailability. Despite the significant progress made, challenges still exist in understanding the genetic factors that influence phytochemical biosynthesis and in optimizing the metabolic transformations induced by processing. Future research should adopt multi-omics approaches to elucidate biosynthetic pathways, use kinetic modeling to reduce the degradation of bioactive compounds, and develop CRISPR-based strategies for improving germplasm. This comprehensive framework bridges fundamental phytochemistry with translational applications, positioning B. juncea as a sustainable resource for functional food innovation and precision health solutions.